Antimicrobial activity of tellurium‐loaded polymeric fiber meshes. Issue 25 (8th March 2018) - Matharu, Rupy Kaur; Charani, Zhalan; Ciric, Lena; Illangakoon, Upulitha Eranka; Edirisinghe, Mohan
ABSTRACT: A series of poly(methyl methacrylate) solutions loaded with varying concentrations of tellurium particles are prepared and processed into continuous and smooth microfiber meshes. Scanning electron microscopy and energy‐dispersive X‐ray spectroscopy are used to study the morphology and surface elemental composition of the composite fibers. Fiber diameters range between 7 and 14 µm with surface nanopores on the fibers ranging between 100 and 200 nm. Energy‐dispersive X‐ray spectroscopy confirmed successful incorporation of tellurium particles into the fibers. The concentration of tellurium in the composite significantly influenced fiber diameter, pore size, and morphology. The antibacterial activity of the prepared fibers is tested using Escherichia coli K12. The fibers are incubated in bacterial suspensions for 24 h at 37 °C and 150 rpm. Antibacterial activity is assessed through the colony‐counting method and is found to be dose dependent. The fibers with 4 wt % tellurium exhibited the most potent antibacterial properties as a 1.16 log reduction was observed. © 2018 The Authors. Journal of Applied Polymer Science Published by Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46368. Abstract :